2017
DOI: 10.3390/e19090495
|View full text |Cite
|
Sign up to set email alerts
|

On the Capacity and the Optimal Sum-Rate of a Class of Dual-Band Interference Channels

Abstract: Abstract:We study a class of two-transmitter two-receiver dual-band Gaussian interference channels (GIC) which operates over the conventional microwave and the unconventional millimeter-wave (mm-wave) bands. This study is motivated by future 5G networks where additional spectrum in the mm-wave band complements transmission in the incumbent microwave band. The mm-wave band has a key modeling feature: due to severe path loss and relatively small wavelength, a transmitter must employ highly directional antenna ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…[P1] by associating a Lagrange multiplier to each constraint in (18)- (21), and then deriving and solving the KKT conditions [34]. See Appendix D for details.…”
Section: The Optimal Sum-rate Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…[P1] by associating a Lagrange multiplier to each constraint in (18)- (21), and then deriving and solving the KKT conditions [34]. See Appendix D for details.…”
Section: The Optimal Sum-rate Problemmentioning
confidence: 99%
“…Moreover, the emergence of dual-band modems from Intel [19] and Qualcomm [20], and practical demonstrations such as that in the 3 GHz-30 GHz dual-bands in [4] clearly illustrate the immense potential of such networks. However, few studies have been reported on the information-theoretic limits of multi-user dual-band networks [21], which are crucial in identifying the limits of achievable rates, simplified encoding schemes, etc., in practical dual-band networks. For example, the study on the two-user interference channel over such integrated dual-bands [13] has shown that forwarding interference to the non-designated receivers through the mm-wave links can improve achievable rates considerably.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations